2022
DOI: 10.3389/fpubh.2022.1019092
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported work-related accumulative fatigue of nurses: A cross-sectional study in public hospitals in China

Abstract: ObjectivesWork-related fatigue is a serious safety risk to nurses and their patients. This study aimed to assess self-reported work-related accumulative fatigue of nurses and its associated factors.MethodsA questionnaire survey of 2,918 clinical nurses conveniently sampled from 48 public hospitals across six provinces in China was conducted. The “Self-diagnosis Checklist for Assessment of Workers' Accumulated Fatigue” was adopted to assess the level of work-related accumulative fatigue of the study participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The association between QWL and turnover intention is echoed by the sociodemographic and work-related predictors of turnover intention revealed in our study, such as workplace violence, sleep deprivation, and lower levels of professional title. Overload has been found to be associated with accumulative fatigue ( 41 ), increased occupational injuries ( 42 ), and higher turnover intention ( 43 ) in nurses in previous studies. Night shifts are common in nursing jobs, which can result in night sleep deprivation and shift work disorder (SWD), leading to ill health, reduced working capacity, and turnover intention ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 85%
“…The association between QWL and turnover intention is echoed by the sociodemographic and work-related predictors of turnover intention revealed in our study, such as workplace violence, sleep deprivation, and lower levels of professional title. Overload has been found to be associated with accumulative fatigue ( 41 ), increased occupational injuries ( 42 ), and higher turnover intention ( 43 ) in nurses in previous studies. Night shifts are common in nursing jobs, which can result in night sleep deprivation and shift work disorder (SWD), leading to ill health, reduced working capacity, and turnover intention ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 85%
“…Another study conducted in a public hospital in China reported that about one-third of the nurses had mild accumulated occupational fatigue, whereas 23.1% had high and 24.6% had very high accumulated occupational fatigue. 30 Similarly, Cho et al 31 reported that the participating nurses had high acute and moderate to high chronic fatigue. Min et al 15 found that nurses' acute and chronic occupational fatigue scores were high, and the inter-shift recovery scores were low.…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-six studies that individual capability plays a role in work-related fatigue among nurses. There was a strong relationship between work experience and work-related fatigue, especially 5-10 years of nursing work experience [21,24,28,45,48,50] . In addition, Seniority and position were statistically signi cant in relation to a high risk of personal and workrelated fatigue [33] .…”
Section: Individual Capabilitymentioning
confidence: 99%
“…There is a correlation between occupational fatigue and the safety climate [31,41] . The work environment emerged as a signi cant predictor of high levels of nurse' fatigue [21,22,57] .…”
Section: 5related Factors Of Work-related Fatiguementioning
confidence: 99%
See 1 more Smart Citation